2018
DOI: 10.7554/elife.32041
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type heterogeneity in the early zebrafish olfactory epithelium is generated from progenitors within preplacodal ectoderm

Abstract: The zebrafish olfactory epithelium comprises a variety of neuronal populations, which are thought to have distinct embryonic origins. For instance, while ciliated sensory neurons arise from preplacodal ectoderm (PPE), previous lineage tracing studies suggest that both Gonadotropin releasing hormone 3 (Gnrh3) and microvillous sensory neurons derive from cranial neural crest (CNC). We find that the expression of Islet1/2 is restricted to Gnrh3 neurons associated with the olfactory epithelium. Unexpectedly, howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…Cell counting of E11.5 and E12.5 Islet-1/2/GnRH co-stained animals revealed that ∼16-23% of the GnRH neuronal population was Islet-1/2(−) (Figure 1I). These results contrast the recent findings in zebrafish where all GnRH cells in the olfactory placode were positive for Islet-1/2 (Aguillon et al, 2018). The percentage of Islet-1/2(−) GnRH neurons (16% in E11.5 and 23% in E12.5) was close to the percentage of GnRH subpopulation proposed to arise from NC progenitors (∼30%, Forni et al, 2011), using Wnt1-cre/Rosa-YFP mouse line as a NC linage tracer (Forni et al, 2011).…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…Cell counting of E11.5 and E12.5 Islet-1/2/GnRH co-stained animals revealed that ∼16-23% of the GnRH neuronal population was Islet-1/2(−) (Figure 1I). These results contrast the recent findings in zebrafish where all GnRH cells in the olfactory placode were positive for Islet-1/2 (Aguillon et al, 2018). The percentage of Islet-1/2(−) GnRH neurons (16% in E11.5 and 23% in E12.5) was close to the percentage of GnRH subpopulation proposed to arise from NC progenitors (∼30%, Forni et al, 2011), using Wnt1-cre/Rosa-YFP mouse line as a NC linage tracer (Forni et al, 2011).…”
Section: Resultscontrasting
confidence: 97%
“…Although the GnRH neuroendocrine population does not receive a contribution from the adenohypophyseal region in mouse (Metz and Wray, 2010), a dual lineage is consistent with ectoderm and NC contributions. A recent study in zebrafish (Aguillon et al, 2018), however, concluded that all zebrafish GnRH3 neurons have a homogenous origin from ectodermal progenitors based on co-labeling with an antibody that recognized Islet-1/2.…”
Section: Introductionmentioning
confidence: 99%
“…1E-H'), further raises the possibility of using this transgenic line to identify new types of cells that derive from the CNC. For example, there is published evidence supporting a CNC origin for the gonadotropin releasing hormone positive and microvillous neurons in the early zebrafish olfactory epithelium, but a most recent study suggests that all the sensory neurons in the zebrafish olfactory epithelium derive from the preplacodal ectoderm instead 22,57,58 . Interestingly, we observed clear eGFP expression in the olfactory epithelium of snail2::egfp tadpoles starting at stage ~42, when the microvillous neurons just emerge 59…”
Section: Discussionmentioning
confidence: 99%
“…The origins of microvillous sensory neurons, however, remain controversial. Our previous work showed that cranial NCCs migrate into the zebrafish OE to form the vast majority of microvillous sensory neurons (Saxena et al, 2013), while fate-mapping work from other groups across multiple species yielded both supportive (Forni et al, 2011;Katoh et al, 2011;Schott et al, 2018) and contradictory (Aguillon et al, 2018) findings, due, in part, to different assumptions about progenitor cell domains. Additionally, recent work suggests that neural plate border cells have greater than expected plasticity, with no clear demarcation between future placodal or NC cells (Roellig et al, 2017), adding further ambiguity to the debate.…”
Section: Introductionmentioning
confidence: 99%